OFFSHORE RENEWABLE ENERGY DEPLOYMENT IN MALAYSIA: A SURVEY STUDY - Azmim, Mohamad Ridzwan (Universiti Teknologi PETRONAS, 2020)
Malaysian seawater has abundant of offshore energy resources as the rest of the places and it would be a waste if it is not being utilize. Offshore renewable energy has a ton of untapped potential that could mitigate one of the most important environmental problems — global warming — and deliver great alternatives. This offshore energy is also considered to be one of the latest, renewable energy alternatives for the existing coal or fossil fuel energy supply. The problem encountered for this study is that the level of knowledge and awareness of Malaysian towards offshore renewable energy and the deployment is unknown. This paper presents the Malaysian community responses using survey study on the deployment of offshore renewable energy in Malaysia. The objectives of this study are to perform survey to measure the knowledge and awareness level of the community towards offshore renewable energy among Malaysians and to quantify the willingness of the community in supporting offshore renewable energy. Thus, a questionnaire-style survey via online was chosen due to the practicality of performing a survey in midst of a pandemic outbreak